A decision approach for multi-stage combined design of solid rocket. Issue 8 (14th September 2021) - Meng, Yanli; Wang, Li; Wang, Lidong
ABSTRACT: The selection and evaluation of solid rocket multi-stage combined schemes with multiple attributes are main issues needed to be resolve. This paper innovatively applied the power generalised compensative weighted averaging (PGCWA) aggregation operator to help multi-stage combined solid rocket select optimal compositional scheme among multiple schemes under multi-attribute environment. The attribute values of each scheme of solid rocket are aggregated to evaluate the scheme, where the weight of attributes is incorporated into the aggregation procedures. Numerical example verifies the proposal method exhibits sound performances in decision support of the aerospace field, the effectiveness and feasibility are further illustrated.